2016
DOI: 10.1002/path.4807
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin in pelvic fluid rescues Fallopian tube epithelial cells from reactive oxygen species stress and apoptosis

Abstract: Fallopian tube fimbrial epithelium is considered to be the major site of origin of ovarian high-grade serous carcinoma, with p53 loss being the earliest and universal change. We previously reported that reactive oxygen species (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…This lesion shares identical p53 mutations and other genomic changes with HGSC, but lacks excessive cell proliferation (16). p53 signature is seen predominantly in continuity with STIC, localizes to the same (fimbria) region as STIC and shares preneoplastic properties with HGSC including p53 mutations (5,17). p53 signature is frequently identified in serous cancer (66%) and may promote p53-driven preneoplastic transformation (12).…”
Section: Histopathology Of Precursor Lesionsmentioning
confidence: 99%
“…This lesion shares identical p53 mutations and other genomic changes with HGSC, but lacks excessive cell proliferation (16). p53 signature is seen predominantly in continuity with STIC, localizes to the same (fimbria) region as STIC and shares preneoplastic properties with HGSC including p53 mutations (5,17). p53 signature is frequently identified in serous cancer (66%) and may promote p53-driven preneoplastic transformation (12).…”
Section: Histopathology Of Precursor Lesionsmentioning
confidence: 99%
“…In studying the transformation of the human fimbrial epithelial secretory cell, the presumed cell-of-origin of HGSOC, studies have used immortalized fimbrial epithelial cells for transformation [8,28,29] and showed clonal expansion and stemness activation on these p53/Rb-deficient FTEC. Although these studies clearly indicated fallopian tube epithelial cells follow the classical tumor evolution from precancerous to a cancerous development, they did not prove the very early step of tumor initiation, which is the transformation of the fallopian tube stem cell.…”
Section: Discussionmentioning
confidence: 99%
“…These observations, together with the tubal origin of most HGSCs, are shifting the focus to how OCPs affect the biology of the FTE, either directly (through their action on estrogen and progesterone receptors in the tubal epithelium and stroma) or indirectly (by preventing ovulation and thereby exposure of fimbrial epithelium to potentially toxic and pro-inflammatory follicular fluid 40, 41 and blood from the ruptured follicle or retrograde menstrual fluid. 42 …”
Section: Primary Prevention Strategiesmentioning
confidence: 99%
“…44 The protective effect afforded by tubal ligation on HGSC could also be a result of decreased blood flow to or atrophy of the distal end of the fallopian tube or by decreased exposure of the fimbrial epithelium to blood in retrograde menstrual fluid. 42 …”
Section: Primary Prevention Strategiesmentioning
confidence: 99%